Scoping review: Neglect of the elderly by nuclear family members: 10.55131/jphd/2022/200221 - Felix, Mark Stephan; Kitcharoen, Patreeya; Cheurprakobkit, Sutham; Le, Thi Ngoc Phuc; Guo, Haihu; Jin, Weiyun (Journal of Public Health and Development, 2022)
Neglect of the elderly in the context of a global aging population is of concern, more so neglect caused to the elderly by nuclear family members. However, the literature on the subject of neglect of the elderly by nuclear family members has yet to be mapped out to afford academics insight into future research directions on the subject. Therefore, a scoping review guided by the PRISMA-ScR checklist was undertaken and mapped out the relevant literature, identified gaps and made suggestions on the subject of neglect of the elderly by nuclear family members. To gain a wider range of possible sources of evidence, the Thai Journals Online (ThaiJO) and China National Knowledge Infrastructure (CNKI) were searched in tandem with the English-Language based Wiley Online Library and ScienceDirect databases. The databases were searched for academic articles published between July 2011 and mid-July 2021. The screening process reduced the initial 975 articles found to 15 sources of evidence. The content of these 15 sources of evidence was mapped out and synthesized via a charting table. Gaps identified include how and why physical necessities are withheld from the elderly; how financial restraints on the elderly by nuclear family members occur; the interplay between finances and neglect; how stress levels, family dynamics, family history and living conditions exacerbate psychological neglect; and, a needed exploration of the forms of verbal neglect perpetrated on the elderly by nuclear family members. Suggestions for future research based on these identified gaps were discussed and offered in this manuscript.